2021
DOI: 10.1111/os.12988
|View full text |Cite
|
Sign up to set email alerts
|

Full‐Endoscopic Approach Forchronic Low Back Pain from Baastrup's Disease: Interspinous Plasty

Abstract: The objective was to introduce a new endoscopic technique‐interspinous plasty for low back pain from Baastrup's disease; based on clinical manifestations, imaging findings and diagnostic test, to discuss a detailed diagnostic procedure for Baastrup's disease; and to explore the mechanism of interspinous plasty in pain relief. To our knowledge, there is no report about the results of endoscopic lumbar technique for Baastrup's disease. This study described the successful full‐endoscopic surgical treatment for Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
2
0
3
Order By: Relevance
“…Other studies continue to demonstrate the value of either partial or complete resection of the spinous processes leading to a complete recovery with a follow-up of up to 2.5 years [ 16 , 17 ]. As a minimally invasive approach, an endoscopic partial resection demonstrated clinical improvements in the visual analog scale and Oswestry disability index scores [ 18 ]. None of the studies showed surgically associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies continue to demonstrate the value of either partial or complete resection of the spinous processes leading to a complete recovery with a follow-up of up to 2.5 years [ 16 , 17 ]. As a minimally invasive approach, an endoscopic partial resection demonstrated clinical improvements in the visual analog scale and Oswestry disability index scores [ 18 ]. None of the studies showed surgically associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…El tratamiento del síndrome de Baastrup es un tema de debate constante a nivel internacional, algunos autores recomiendan el uso de infiltraciones percutáneas con corticosteroides de acción prolongada y en ocasiones anestésicos locales para tratar la inflamación y el dolor, cuyos resultados han mostrado una mejora significativa en las puntuaciones de dolor a más de un año después del tratamiento. 6,7 Se mencionan además técnicas quirúrgicas resectivas y no resectivas (dispositivos interlaminares o ablaciones por radiofrecuencia) con resultados variables entre diversos autores. En 1944, Franck y colaboradores describieron su experiencia con la resección parcial de las apófisis espinosas realizada en 10 pacientes; 2 encontraron recuperación completa en 40%, mejoría clínica en otro 40% y el restante 20% no presentó cambios; destacaron que los pacientes que no respondieron al tratamiento tenían comorbilidades vertebrales como fracturas que podrían explicar la persistencia del dolor.…”
Section: Discussionunclassified
“…Algunos autores recomiendan el uso de infiltraciones percutáneas con corticosteroides de acción prolongada y en ocasiones, anestésicos locales para tratar la inflamación y el dolor, cuyos resultados han mostrado una mejora significativa en las puntuaciones de dolor a más de un año después del tratamiento. 6,7 Además, se mencionan técnicas quirúrgicas resectivas y no resectivas (dispositivos interlaminares o ablaciones por radiofrecuencia) con resultados variables entre diversos autores. 6,8,9…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It is prevalent among middle-aged and older people with slow progression. It is characterized by hypertrophy of the spinous process as imaging features and often causes low back pain [ 22 24 ]. The lateral radiographs of the patients revealed that their spinous processes were consistent with each other and had corresponding bone sclerosis.…”
Section: Discussionmentioning
confidence: 99%